مستوى توظيف معلمي اللغة العربية في الأردن كفايات التعليم الإلكتروني في ضوء الكفايات الإلكترونية المنشودة لمعلم المستقبل - الزبون، أحمد محمد عقلة (جامعة الملك خالد - كلية التربية - مركز البحوث التربوية, 2018)
هدفت الدراسة الكشف عن مستوى توظيف معلمي اللغة العربية في الأردن كفايات التعليم الإلكتروني. ولتحقيق أهداف الدراسة تم تطوير استبانة مكونة من (٣٣) فقرة، موزعة على ثلاثة مجالات، تكونت عينة الدراسة من (250) معلمًا ومعلمة، تم اختيارهم بالطريقة المقصودة خلال الفصل الدراسي الثاني (2013/ 2014)، وأشارت نتائج الدراسة إلى أن مستوى توظيف معلمي اللغة العربية في الأردن كان متوسطا، كما بينت نتائج الدراسة وجود فروق ذات دلالة إحصائية في مجال التخطيط للعملية التعليمية تعزي إلى متغير الجنس ولصالح الإناث، ووجود فروق ذات دلالة إحصائية في مجال تقويم العملية التعليمية تعزي إلى متغير الدورات التدريبية ولصالح دورة (ENTEL) وأثبتت الدارسة -أيضا - عدم وجود فروق ذات دلالة إحصائية في مجالات الدراسة تعزى إلى متغير المؤهل العلمي. وأوصى الباحث بالإكثار من الدورات المتخصصة في مجال الحاسوب وتكنولوجيا المعلومات؛ مثل: دورات ICDL، ودورات (ENTEL)، وغيرها من الدورات التي تمكن معلمي اللغة العربية من امتلاك كفايات تطبيق التعليم الإلكتروني.
The study aimed at investigating the level of Arabic teachers' employment of electronic competencies in Jordan. To achieve the objectives of the study, the researcher developed a questionnaire which consisted of (33) items and was divided into three fields. The study sample consisted of (250) teachers, who were selected purposefully during the second semester of 2013 / 2014 AD. The findings revealed that the level of employment of Arabic language teachers of electronic skills in Jordan was average. The results also showed that, there were statistically significant differences in the field of the planning for the educational process related to the gender variable favoring female teachers. The result of the study also revealed that there were statistically significant differences in the field of evaluation of the teaching process related to the training courses variable favoring (ENTEL) courses. The study also proved that there were no statistically significant differences in the fields of the study related to the educational qualifications variable. The researcher recommended that a great deal of specialized courses in the field of computer and information technology, such as ICDL courses, (ENTEL) courses, and other courses that enable teachers of Arabic language to acquire the skills of application of e-learning should be introduced.
Keywords: الكفايات التعليمية -- معلمو اللغة العربية -- الأردن -- الكفايات الإلكترونية -- التعليم الإلكتروني -- استشراف المستقبل